2016
DOI: 10.1093/fpa/orw035
|View full text |Cite
|
Sign up to set email alerts
|

Democratic Participation in the Air Strikes Against Islamic State: A Qualitative Comparative Analysis

Abstract: Although over sixty partners have joined the US-led coalition against the Islamic State (IS), only a handful of states was willing to carry out air strikes against IS-targets. This article aims to explain the pattern of democratic participation in the air campaign. It builds on the rich literature on military burden sharing and democratic peace theory to develop a multi-causal model, which is tested with Qualitative Comparative Analysis. The results of the analysis suggest that the pattern of participation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 66 publications
3
38
0
1
Order By: Relevance
“…Taken together, they demonstrate how a combination of sceptical public opinion, strong parliamentary war powers, and party constellations in parliament and government can contribute to military restraint. In line with these findings, Haesebrouck (2016) shows that a causal condition for military involvement against Islamic State of Iraq and Syria (ISIS)/ Daesh was the absence of parliamentary war powers.…”
Section: Comparing Effects Of Parliamentary Involvement On Governmentsupporting
confidence: 63%
See 1 more Smart Citation
“…Taken together, they demonstrate how a combination of sceptical public opinion, strong parliamentary war powers, and party constellations in parliament and government can contribute to military restraint. In line with these findings, Haesebrouck (2016) shows that a causal condition for military involvement against Islamic State of Iraq and Syria (ISIS)/ Daesh was the absence of parliamentary war powers.…”
Section: Comparing Effects Of Parliamentary Involvement On Governmentsupporting
confidence: 63%
“…Classifications of parliamentary competences have been used to account for decisions on war involvement in individual conflicts (Dieterich et al, 2015;Haesebrouck, 2016;Mello, 2014). These studies found that parliamentary competences alone do not suffice to explain government's propensity to deploy troops but that interactions with other factors need to be considered, especially public opinion and the partisan composition of parliament and government.…”
Section: Constitutional Rules and The Role Of Parliaments In Sending mentioning
confidence: 99%
“…14 The period of substantial representation in parliament and, consequently, the number of observations varies across the parties: RC (1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)66), PdCI (1998PdCI ( -2008, DS (1994DS ( -2006, PD (2006-16, 38) PPI/La Margherita (1994, CCD/CDU (1994-2001, UDC (2001-13, 59), FI-PdL (1994-2016, AN (1994, LN (1994LN ( -2016. 15 We decided to sum the votes of DS and La Margherita, establishing a continuity with PD (which is the result of their merger) to increase the number of observations.…”
Section: Discussionmentioning
confidence: 99%
“…Parliamentary Support in Key Votes (1994-2016 Note: Country of mission, year, chamber, with C and S standing for Chamber of Deputies and Senate, respectively. Fabrizio Coticchia and Valerio Vignoli https://doi.org/10.1017/gov.2018.…”
mentioning
confidence: 99%
“…In addition, several parliaments that could have vetoed participation did not do so. Haesebrouck (2016a , 2016b ) has used a very similar research design to examine the contributions of liberal democracies to the United Nations Interim Force in Lebanon (UNIFIL) and to the air strikes against Daesh. As regards to UNIFIL, he finds that ‘the presence of parliamentary veto […] is associated with the absence of large contributions’ ( Haesebrouck, 2016b : 152).…”
Section: State Of the Artmentioning
confidence: 99%